Impact of Pre-operative Embolization With Onyx for Brain Arteriovenous Malformation Surgery - Izumo, Tsuyoshi; Okamura, Kazuaki; Takahira, Ryotaro; Matsunaga, Yuki; Sadakata, Eisaku; Maeda, Hajime; Yamaguchi, Susumu; Baba, Shiro; Morofuji, Yoichi; Hiu, Takeshi; Horie, Nobutaka; Anda, Takeo; et al. (Frontiers in Neurology, 2022)
Objective To clarify the safety and efficacy of pre-operative embolization using Onyx liquid embolic agent (Onyx; ev3) compared with N-butyl cyanoacrylate (NBCA; Cordis Neurovascular, Inc.) or coils in cerebral arteriovenous malformation (AVM) surgery. Methods This was a retrospective review of a prospectively collected clinical database of brain AVMs treated at our institute from January 2005 to March 2021. A total of 38 consecutive patients who underwent AVM resection after pre-operative embolization were included. Based on pre-operative embolization materials, the patients were divided into the pre-Onyx group (n = 16), in which NBCA or coils were used for embolization, and the Onyx group (n = 22). Patient characteristics and treatment results were compared between the two groups. Results Patient characteristics were comparable between the two groups in terms of age, sex, and rupture status. While the Spetzler–Martin grade was also similar between the two groups, the location of the AVM nidus in the eloquent area was slightly higher in patients in the Onyx group (72.7%) than in patients in the pre-Onyx group (43.8%) (P = 0.09). The embolization rate was higher in the pre-Onyx group (mean: 63.0%; range: 12.7–100%) than in the Onyx group (mean: 50.0%; range: 15.8–100%), but the difference was not statistically significant (P = 0.06). The time needed for surgical removal was shorter in the Onyx group (mean: 354.8 min; range: 144–884 min) than in the pre-Onyx group (mean: 457.9 min; range: 240–1,294 min); however, this difference was not statistically significant (P = 0.13). The amount of intraoperative bleeding was significantly lower in the Onyx group (mean: 129.8 ml; range: 20–540 mL) than in the pre-Onyx group (mean: 448.8 mL; range: 120–1,550 ml) (P = 0.0008). The surgical complication rates were comparable between the two groups (pre-Onyx group, 18.8%; Onyx group, 4.5%; P = 0.29). Conclusions Pre-operative embolization with Onyx can significantly reduce the amount of intraoperative bleeding in AVM resection and may contribute to safe AVM surgery.